Membangun Generasi Tanpa Perundungan: Edukasi Anti-Bullying Bagi Remaja di Kelurahan Kebon Lega - Febrianti, Friska (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
Bullying remains a serious issue among children and adolescents, causing negative impacts on psychological well-being, academic performance, and social development. To address this, an anti-bullying education program was conducted at Kebon Lega using a seminar method as a form of non-formal, knowledge-based education. Participants gained understanding of the definition, forms, impacts, and strategies for preventing and handling bullying. The results showed an increase in participants’ knowledge, the growth of empathy and social awareness, and a collective commitment to creating a safe and bullying-free environment. Community involvement further strengthened the dissemination of positive values, making this activity effective in raising collective awareness for bullying prevention.